Reforming the French Law of Obligations - Cartwright, J (Hart Publishing, 2009)
The 2005 Avant-projet de réforme du droit des obligations et de la prescription, also dubbed the Avant-projet Catala, suggests the most far-reaching reform of the French Civil code since it came into force in 1804. It reviews central aspects of contract law, the law of delict and the law of unjustified enrichment. There is currently a very lively debate in France as to the merits or the demerits of both the particular draft provisions and the general idea of recodification as such. This volume is the first publication to introduce the reform proposals to an English speaking audience. It contains the official English translation of the text, and distinguished private lawyers from both England and France analyse and assess particularly interesting aspects of the substantive draft provisions in a comparative perspective. Topics covered include negotiation and renegotiation of contracts, la cause, the enforcement of contractual obligations, termination of contract and its consequences, the effects of contracts on third parties, the definition of la faute, the quantification of damages, and the law of prescription. The volume also contains an overall assessment of the draft provisions by one of the most senior French judges who chaired the Working Party on the Avant-projet, established by the French Supreme Court, the Cour de cassation. The book is indispensable for comparative private lawyers and lawyers with a particular interest in French law. It is also of use to all private lawyers (both academics and practitioners) looking for information on recent international and European trends in contract and tort.